PELATIHAN SENAM HAMIL PADA IBU HAMIL TRIMESTER III UNTUK MENCEGAH LAMA WAKTU PERSALINAN KALA I DI TPMB. NENENG HALIMATUL SA’DIAH CIKARANG SELATAN TAHUN 2025 - Yuli Erlina; Ermaya Sari Bayu Ningsih2 (Bajang Institute, 2025)
Gymnastics is a pregnant undertaken to prevent the long delivery, the majority of obstructed labor is delivery long (30 %) and now 6 hours before delivery (19 %) was born that led to the birth mother with sectio caesarrea. Gymnastics pregnant is one effort to support ease in childbirth and for providing the third trimester of pregnancy. Gymnastics pregnant too can exercise various respiratory technique important that delivery make it run successfully and faster, and speed of weight loss of women after delivery. The aim of this community service activity is to provide Pregnancy Exercise training to increase the knowledge and skills of pregnant women to prevent prolonged first stage labor at TPMB. Neneng Halimatul Sa'diah South Cikarang, so that pregnant women are able to do pregnancy exercises to improve knowledge and health during pregnancy and childbirth. Implementation method: method used in service activities with lectures, and simulations or role plays. Community service activities were carried out on July 17 2025 at TPMB. Neneng Halimatul Sa'diah, South Cikarang. It is hoped that the results of this community service activity can become the basis for the knowledge and skills of pregnant women to be able to prevent incidents of prolonged labor.